Multifunctional UMP drone new technology in agriculture sector - Nor Salwana, Mohammad Idris (2022)
PEKAN, 21 May 2022 - A team of researchers from the Centre for Design and Innovation of Technology (PRInT), Universiti Malaysia Pahang (UMP) successfully produced a multifunctional drone using local expertise known as ‘Rajawali’ to expand innovation and use of new technologies in increasing the productivity of the agricultural sector.